Analisis Implementasi Arsip Digital Dokumen Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Bandung - Qolby, Apriliany Nur; Taufik, Yuyun (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2025)
This study examined the implementation of digital archiving at the DPMPTSP Kota Bandung and its impact on administrative processes, transparency, and operational efficiency. The transition from manual to digital archives aimed to improve document accessibility, minimize paper usage, and streamline administrative workflows. Data were collected through interviews with key personnel in different departments, including Administration, Secretariat, Archive Management, and IT. The findings revealed that digital archiving significantly accelerated document retrieval and processing, reducing administrative delays. Paper consumption decreased, particularly in communication and internal documentation, yet some legal processes still required physical documents. Transparency improved as digital tracking ensured accountability and minimized the risk of data loss. Furthermore, real-time document access enhanced work flexibility, although challenges such as network instability and suboptimal storage structures remained. Despite efficiency gains, challenges persisted, including the need for standardized document formats, enhanced cybersecurity measures, and continuous employee training. To maximize the benefits of digital archiving, recommendations included optimizing storage structures, strengthening IT infrastructure, and improving digital literacy among employees. If fully integrated and continuously developed, digital archives could serve as a foundation for a more effective and modern public administration system.